Technological change and its influence on institutional culture at the University of the Witwatersrand, Johannesburg - Habanyana, Dawn (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this research has been to explore the technological change and its influence on institutional culture at the University of the Witwatersrand, Johannesburg. The main problem identified is attributed to by human-dependant manual and paper- based processes that affect the culture of the institution. This research paper selected the university of the Witwatersrand as its case study, as it is one of the leading universities in Africa. A qualitative research methodology was used, where three main research questions were answered based on the chosen case study. Data was collected through face-to-face semi-structured interviews with participants who belonged to the university community. Data collection was analysed, and the finding were presented in phases. The first phase was capturing and reporting on the on the response received from the participants. The second phase is the analysis and interpretation of the data. Then the last phase brought through a clear understanding of the data by presenting the data through categories and themes. The research paper triggered the notion that the COVID 19 pandemic regulations has fast tracked the use and dependency of technology. Making it evident that technological change has its influence on institutional culture especially at the university of the Witwatersrand
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Technological Change; Digital Culture; Higher Education; University of the Witwatersrand; UCTD; SDG-9: Industry, innovation and infrastructure